PENGUJIAN VALIDITAS DAN PRAKTIKALITAS TES DISPOSISI BERPIKIR KRITIS DALAM BIOLOGI (TDBKB) - Jayanti Syahfitri (Pendidikan Kimia Unimus, 2019)
Good instruments are not only seen from validity and reliability but can also be seen from practical values. The purpose of this study is to examine content validity and practicality of critical thinking disposition tests in biology. This study involved 73 biology education students as samples taken from the 1st and 3rd study levels. The instruments used in the study were drafts of critical thinking disposition tests in biology and response questionnaires. This study uses the Content Validity Ratio (CVR) method. A draft critical thinking disposition test in biology was validated by six validators. Based on the findings indicate that the test of critical thinking disposition tests in biology has content validity and good practical value.